Encrypted Storage of Medical Data on a Grid - Seitz, L.; Pierson, J.-M.; Brunie, L. (Methods of Information in Medicine, 2005)
Objectives: In this article we present grids as an architecture for medical image processing and health-care networks. We argue that confidential patient data should not be stored unprotected on a grid and explain why access control systems alone do not offer sufficient protection. The objective of our work is to propose a method that complements access control systems on a grid architecture and thus makes the storage of confidential data more secure.Methods: Effective protection can be achieved by storing confidential data in encrypted form. This raises the problem of how authorized users get access to the data, since they need to have the decryption keys.Results: Our proposal details a key management architecture, that allows encrypted storage and still enables users to access decryption keys for data they are authorized to see. To achieve this functionality we use distributed keyservers storing redundant shares of the keys.Conclusions: The resulting architecture achieves our primary objective of making the storage of confidential data more secure without loosing the data sharing properties of the grid architecture. Furthermore our architecture is robust against breakdowns and denial of service attacks. It scales well with the number of users and does not introduce a single point of failure into the system.
Keywords: Encrypted storage; key management; medical grids; health-care networks